Exploring 21st Century Skills and Learning Environments for Middle School Youth - Annahita Ball; Hillary D Joyce; Dawn Anderson-Butcher (International Journal of School Social Work, 2016)
Resiliency research and strengths-based perspectives highlight the importance of understanding the protective factors that aid youth in overcoming adversity. Likewise, current research identifies the characteristics and skills youth need to be successful in post-secondary education and the workforce. These growing bodies of research emphasize cognitive and noncognitive skills that support youth development and academic success. This exploratory study sought to develop two distinct measurement instruments: (1) the 21st Century Life & Career Skills scale (21C-LCS); and (2) the 21st Century Skills Classroom Environment scale (21C-CE). We also examined students’ perceptions of their own skills in these areas. The measures were developed and tested using survey data from 262 middle school students. Exploratory Factor Analysis was used to examine the factorial structure of the measures and descriptive statistics were used to summarize student perceptions. Results indicated that the 21C-LCS and the 21C-CE are brief psychometrically sound measures. The 21C-LCS assesses students’ leadership and responsibility; working with others effectively; and, adaptability. The 21C-CE is a reliable measure of students’ perceptions of the ways in which their classroom environments support their development of 21st century life and career skills. Students reported moderately high perceptions of their skills in all areas. This study is an important step in measuring 21st century life and career skills and 21st century learning environments. Researchers, youth development professionals, educators, and other service providers can utilize these measures in ongoing investigation, assessment, and progress monitoring to foster and advocate for 21st century life and career skill development among youth.
Keywords: 21st century skills; scale development; life and career skills; learning environment